Benthic foraminifera and brachiopods from a marine cave in Spain: environmental significance - BERGAMIN, LUISA; TADDEI RUGGIERO, EMMA; PIERFRANCESCHI, GIANCARLO; ANDRES, BELEN; CONSTANTINO, RICARDO; CROVATO, CINZIA; D’AMBROSI, ANDREA; MARASSICH, ANDREA; ROMANO, ELENA (Mediterranean Marine Science, 2020)
Sediment samples from a marine cave in the Murcia region (eastern Spain) were analysed for grain size, total benthic foraminifera and dead brachiopoda to obtain environmental information through physical and ecological data in order to understand the benthic communities of cave environments and their ecological significance. A total of 100 foraminiferal and 7 brachiopod species were classified, highlighting the first occurrence in the western Mediterranean of Gwynia capsula (Jeffreys, 1859). Statistical analysis applied to foraminiferal data allowed the identification of three assemblages characterised by decreasing species diversity along the cave. This corresponded to a similar separation recognisable through changes in brachiopod species abundance and well-correlated with cave morphology. The relative abundance of epifaunal clinging-attached foraminifera as well as the rate of cave and sciaphilic/coralligenous Brachiopoda, thought to be representative of the degree of separation from marine conditions, were found to be highly correlated, increasing towards the inner cave. Our hypothesis was that despite the different lifestyles of these two groups, the strict correlation of environmental factors (i.e. light, nutrients, sediment texture, water parameters) changing along the length of the cave determines a comprehensive environmental gradient, causing an increase in environmental stress that has similar effects on the different taxonomic groups.